Optimizing the Morphology and Optical Properties of MoS2 Using Different Substrate Placement: Numerical Simulation and Experimental Verification - Feng Liao; Yuhan Zeng; Qingqing Xie; Yupeng Yang; Shuangyi Linghu; Li Liang; Zewen Zuo (Crystals)
The prerequisite for rapid and steady development of TMDC-based optoelectronic devices is high efficiency in materials preparation, which relies on a mature synthesis technique and optimized production conditions. Visualization based on numerical simulation, which illustrates the impact of growth parameters on deposited products, is helpful to understand formation mechanisms and modify growth conditions. In this work, we construct two models with two different substrate placements, where the substrate is parallel or perpendicular to gas flow direction. The simulation results show more velocity distribution uniformity across a wider range from −1.4 cm to 1.4 cm for vertically placed (VP) compared to horizontally placed (HP) substrates. The calculated average velocities of 0.048, 0.053, 0.078, 0.137, and 0.391 cm/s along five different positions on the VP substrate are greater than the values of 0.027, 0.026, 0.025, 0.023, and 0.036 cm/s on the HP substrate. Comparing the precursor concentration distributions on both substrates, it is observed that the S molar concentration gradient on both substrates is negligible and the uniform Mo molar concentrations from z = −1.4 cm to 2.0 cm on the VP substrate ensure minimal change in the S/Mo ratio, which contributes to forming single-morphology domains. Furthermore, increasing the distance between the precursor inlets and the VP substrate decreases the amount of molecules on the substrate surface, achieving near-stoichiometry and promoting monolayer deposition. This is verified by the experimental result, which showed gentle morphological transformation on the VP substrate from a truncated triangle to a hexagon, and then back to a truncated triangle. By contrast, the multi-morphology and thickness of MoS2 on the HP substrate result from the complex Mo concentration along the flow direction. Moreover, PL intensities of the MoS2 domains deposited on the VP substrate are enhanced by 11.9-fold compared to the average intensity on the HP substrate. This result indicates the MoS2 grown on the VP substrate has less intrinsic defects than that grown on the HP substrate. The combination of numerical simulation with experimental methods facilitates the visualization of invisible growth conditions, which provides effective guidance for using simulation results for other TMDC materials.